Impact of gold price, financial development, renewable energy, economic growth, urbanization, and environmental tax on environmental degradation - Bambi, Prince Dorian Rivel; Pea-Assounga, Jean Baptiste Bernard (Frontiers in Environmental Science, 2025)
This study comprehensively investigates the effects of gold price, financial development, renewable energy consumption, economic growth, urbanization, and environmental taxation on environmental degradation. The analysis is conducted using panel data from nine gold-producing countries in West Africa, covering the period from 2000 to 2020. To ensure the credibility and robustness of the findings, the study employs a range of advanced econometric techniques, including Fully Modified Ordinary Least Squares, Dynamic Ordinary Least Squares, Canonical Cointegrating Regression, Robust Least Squares, and Granger causality tests. The motivation for this research arises from the urgent need to address escalating environmental challenges in West Africa resource-dependent economies, where gold mining remains a key economic driver but simultaneously contributes to significant environmental damage. Therefore, this study aims to provide practical insights that can guide the formulation of sustainable policies that balance economic growth with environmental preservation. The results reveal several important dynamics. Firstly, both financial development and urbanization exert a significant positive influence on environmental degradation, indicating their role in exacerbating ecological pressure. In contrast, economic growth appears to play a mitigating role by helping reduce environmental degradation, suggesting that economic expansion, if managed efficiently, can be aligned with sustainability goals. Moreover, environmental taxation proves to be an effective policy tool in limiting pollution levels, thereby reinforcing its significance as a regulatory mechanism. However, the analysis shows that neither gold price fluctuations nor renewable energy consumption has a direct, statistically significant impact on environmental degradation. Nevertheless, the Robust Least Squares estimates suggest that renewable energy consumption, GDP growth, and urbanization may contribute to environmental improvements under specific conditions. Furthermore, the Granger causality tests reveal notable causal relationships. There is a unidirectional causality running from gold price fluctuations to environmental degradation and from economic growth to environmental sustainability. Interestingly, urbanization and environmental degradation exhibit a bidirectional causal link, implying a feedback loop between these two factors. Additionally, environmental degradation is found to Granger-cause environmental tax implementation, highlighting the reactive nature of policy responses to environmental deterioration. On the other hand, no significant causal connection is detected between financial development, renewable energy consumption, and environmental degradation. Overall, these findings offer valuable insights for policymakers seeking to promote sustainable development pathways in resource-reliant economies. At the same time, the study acknowledges existing limitations and recommends future research to explore these dynamics in broader contexts and with more granular data.